Role of favipiravir in the treatment of COVID-19. (January 2021) - Joshi, Shashank; Parkar, Jalil; Ansari, Abdul; Vora, Agam; Talwar, Deepak; Tiwaskar, Mangesh; Patil, Saiprasad; Barkate, Hanmant
Highlights: Favipiravir is approved by some countries, including India, for COVID-19 treatment. Favipiravir has shown rapid viral clearance and faster clinical improvement. Various treatment recommendations include favipiravir for COVID-19 treatment. Several ongoing clinical trials will further substantiate favipiravir role. Abstract: The coronavirus disease-2019 (COVID-19) outbreak all over the world has led the researchers to strive to develop drugs or vaccines to prevent or halt the progression of this ailment. To hasten the treatment process, repurposed drugs are being evaluated. Favipiravir is one such oral drug that was approved for new and reemerging pandemic influenza in Japan in 2014 and has shown potent in vitro activity against severe acute respiratory syndrome coronavirus-2. It has a wide therapeutic safety margin indicated by a wide CC50/EC50 ratio for a high dose. From the clinical studies in COVID-19, it has shown rapid viral clearance as compared to lopinavir/ritonavir (LPV/RTV) and superior recovery rate than umifenovir. Overall, favipiravir has shown promising results in clinical studies in China, Russia, and Japan, and more trials are underway in multiple countries, including USA, UK, and India. Recently, treatment guidelines from many countries and some states from India have included favipiravir in the treatment protocol. This review provides insights into the evidence-based evolving role of favipiravir in the management of COVID-19 infection with emphasis on benefits of initiating an early antiviral therapy with special focus on favipiravir, its pharmacodynamic, pharmacokinetic, in vitro, clinical data, and inclusion in the treatment protocols of COVID-19.